EFEK HEPATOPROTEKTIF EKSTRAK DAUN KEMUNTING (Rhodomyrtus tomentosa [Aiton] Hassk.) TERHADAP HEPATOTOKSISITAS YANG DIINDUKSI PARASETAMOL - ., Erlin Irawati (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Liver has an important role in drug metabolism whichcause liver as the main target of the damage caused by drugs. There areso many drugs that has been reported to cause hepatotoxicity, one ofthem is paracetamol. Hepatotoxicity can be prevented by hepatoprotectiveagents. Kemunting (Rhodomyrtus tomentosa [Aiton] Hassk.) leaves haspotency as hepatoprotective agent because it has antioxidant biochemicalcontent. Objective: The aim of this study was to determinehepatoprotective effect of Kemunting extract against paracetamolhepatotoxicity. Methodology: This research used maceration with ethanol70% as the extraction method. The research was done in 10 days on maleWistar rats. The rats divided into 6 group; solvent control group (CMC0,5%), negative control (paracetamol 1000 mg/kg bw on the third, seventh,and tenth day), positive control (silymarin 200 mg/kg bw), kemuntingleaves extract doses 200, 400, and 800 mg/kg bw. The rats weresacrificed on the eleventh day to analyze transaminase enzymes (SGOTand SGPT) and liver microscopic. Data was analyzed using One WayAnova test. Results: There were elevations of SGOT and SGPT level withhydrophic degeneration in group given with paracetamol only. Positivecontrol group (silymarin) and kemunting leaves extract group showedminimal recoveries but they were not significant in statistical analysis.Conclusion: The hepatoprotective effect of kemunting extract leaves isinadequate against paracetamol-induced hepatotoxicity. Keyword: Rhodomyrtus tomentosa [Aiton] Hassk., paracetamol,biochemical analysis, liver microscopic 1) Medical Education Program, Faculty of Medicine, University ofTanjungpura Pontianak, West Borneo. Â 2) Pharmacy Program, Faculty of Medicine, University of TanjungpuraPontianak, West Borneo. 3) Department of Physiology, Faculty of Medicine, University ofTanjungpura Pontianak, West Borneo.